Structural Plasticity of Intrinsically Disordered LEA Proteins from Xerophyta schlechteri Provides Protection In Vitro and In Vivo - Artur, Mariana A. Silva; Rienstra, Juriaan; Dennis, Timothy J.; Farrant, Jill M.; Ligterink, Wilco; Hilhorst, Henk (Frontiers in Plant Science, 2019)
Late Embryogenesis Abundant proteins (LEAs) are essential to the ability of resurrection plants and orthodox seeds to protect the subcellular milieu against irreversible damage associated with desiccation. In this work we investigated the structure and function of six LEAs expressed during desiccation in the monocot resurrection species Xerophyta schlechteri (XsLEAs). In silico analyses suggested that XsLEAs are hydrophilic proteins with variable intrinsically disordered protein (IDP) properties. Circular dichroism (CD) analysis indicated that these proteins are mostly unstructured in water but acquire secondary structure in hydrophobic solution, suggesting that structural dynamics may play a role in their function in the subcellular environment. The protective property of XsLEAs was demonstrated by their ability to preserve the activity of the enzyme lactate dehydrogenase (LDH) against desiccation, heat and oxidative stress, as well as growth of Escherichia coli upon exposure to osmotic and salt stress. Subcellular localization analysis indicated that XsLEA recombinant proteins are differentially distributed in the cytoplasm, membranes and nucleus of Nicotiana benthamiana leaves. Interestingly, a LEA_1 family protein (XsLEA1-8), showing the highest disorder-to-order propensity and protective ability in vitro and in vivo, was also able to enhance salt and drought stress tolerance in Arabidopsis thaliana. Together, our results suggest that the structural plasticity of XsLEAs is essential for their protective activity to avoid damage of various subcellular components caused by water deficit stress. XsLEA1-8 constitutes a potential model protein for engineering structural stability in vitro and improvement of water-deficit stress tolerance in plants.